ANTI-RASISME DALAM NOVEL PERJALANAN BURMESE DAYS KARYA GEORGE ORWELL - Fitrilya Anjarsari (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2015)
Abstract This research is aimed to analyze Orwell’s role in writing a travel writing. Shifting in type, main story, and function of a travel writing leads the researcher to reveal Orwell’s position in it. Approach applied in this research is the concept of negotiation; self and othering by Carl Thompson. It will help the researcher to find out the position and role of Orwell in seeing and responding to apartheid political situation (racism) in Burma. This will also directly reveal the tendential influences existing in Orwell himself.Keywords: Racism, Travel Writing, Negotiation, Self and Othering